Role of antisecretory drug in treatment of children with acute watery diarrhea: A Randomized Controlled Trial - Reham M Sayed; Hosny M.A El-Masry; Ismail Abd El-Razek Kasem (Wolters Kluwer Medknow Publications, 2022)
Background and aim Previous studies have shown that Racecadotril is safer and more effective in treating children with acute diarrhea. This study aimed to evaluate the effect of Racecadotril as a booster to oral rehydration solution in the management of acute watery diarrhea among children aged 5 years or less. Patients and methods This random clinical trial included 50 children with acute watery diarrhea for less than or equal to 5 days with a frequency of more than or equal to three diarrheic stools in the past 24 h before admission to the hospital, with no mild-to-moderate dehydration. Our study is registered to clinicaltrials.gov (NCT05216822). Results The main findings of this study were that Racecadotril reduced the duration of the diarrheal episodes and the duration of hospitalization significantly. This study revealed that Racecadotril showed an improvement in the consistency of stool, which protects the patient from fluid loss and dehydration. Conclusion Racecadotril is an effective booster-rehydration drug that carries out its antidiarrheal effect by inhibiting intestinal enkephalinase. It is efficient in reducing the volume and frequency of stool output.